The Prognosis and Feasibility of Extensive Clinical Target Volume in Postoperative Radiotherapy for Esophageal Squamous Cell Carcinoma: A Phase II Clinical Trial - Zhang, Xiaofei; Ai, Dashan; Wang, Juanqi; Chen, Yun; Liu, Qi; Deng, Jiaying; Yang, Huanjun; Nie, Yongzhan; Chen, Weiwei; Zhao, Weixin; Zhao, Kuaile (Frontiers in Oncology, 2021)
BACKGROUND: This trial aims to explore the feasibility and safety of postoperative radiotherapy covering all regional lymph node areas for locally advanced thoracic esophageal squamous cell carcinoma patients treated with intensity-modulated radiation therapy (IMRT). METHODS: This was a single-center single-arm, phase II clinical trial initiated in 2014. Patients who were treated with radical transthoracic resection and had negative margins within 3 months and histologically confirmed esophageal squamous cell carcinoma (pT3-4 or N+, M0 determined by the 7th edition of the AJCC guidelines) were recruited in this trial. Postoperative radiotherapy was performed with a total dose of 40 Gy in 20 fractions using IMRT. Clinical target volumes (CTVs) included the tumor bed, anastomosis, bilateral supraclavicular region, mediastinal lymph nodes, left gastric lymph nodes and celiac trunk lymph nodes. The primary endpoint was the 2-year local control rate, and the secondary endpoints were overall survival (OS) and adverse events (AEs). RESULTS: A total of 70 eligible patients were recruited from 2014 to 2016. The 2-year local control rate, as the primary endpoint, was 67.3%. In addition, the median OS was 57.0 months, with 1-year and 3-year OS rates of 92.8% and 60.9%, respectively. Among the patients, 28/40 (40%) developed locoregional recurrence, with 25.7% involving hematogenous recurrences. All reported AEs occurred during the course of IMRT or within 6 months thereafter. None of them suffered grade 4 hematological or nonhematological AEs. Nearly all patients completed the entire course of postoperative radiotherapy, with a completion rate of 97.1%. CONCLUSION: For an extensive target volume, 40 Gy is feasible and shows acceptable toxicity in patients with locally advanced thoracic esophageal squamous cell carcinoma, although the local recurrence rate is relatively high. Our findings provide a basis for further exploration of high-dose radiation with extensive CTV combined with chemotherapy. TRIAL REGISTRATION: This study was registered in NCT on 10 March 2015 (NCT02384811, (http://www.clinicaltrials.gov/ct2/results?cond=&term=NCT02384811&cntry=&state=&city=&dist=).